Myotonic Myopathy With Secondary Joint and Skeletal Anomalies From the c.2386C>G, p.L796V Mutation in SCN4A - Elia, Nathaniel; Nault, Trystan; McMillan, Hugh J.; Graham, Gail E.; Huang, Lijia; Cannon, Stephen C. (Frontiers in Neurology, 2020)
The phenotypic spectrum associated with the skeletal muscle voltage-gated sodium channel gene (SCN4A) has expanded with advancements in genetic testing. Autosomal dominant SCN4A mutations were first linked to hyperkalemic periodic paralysis, then subsequently included paramyotonia congenita, several variants of myotonia, and finally hypokalemic periodic paralysis. Biallelic recessive mutations were later identified in myasthenic myopathy and in infants showing a severe congenital myopathy with hypotonia. We report a patient with a pathogenic de novo SCN4A variant, c.2386C>G p.L769V at a highly conserved leucine. The phenotype was manifest at birth with arthrogryposis multiplex congenita, severe episodes of bronchospasm that responded immediately to carbamazepine therapy, and electromyographic evidence of widespread myotonia. Another de novo case of p.L769V has been reported with hip dysplasia, scoliosis, myopathy, and later paramyotonia. Expression studies of L796V mutant channels showed predominantly gain-of-function changes, that included defects of slow inactivation. Computer simulations of muscle excitability reveal a strong predisposition to myotonia with exceptionally prolonged bursts of discharges, when the L796V defects are included. We propose L769V is a pathogenic variant, that along with other cases in the literature, defines a new dominant SCN4A disorder of myotonic myopathy with secondary congenital joint and skeletal involvement.